Comparison of the Effectiveness of Problem-Solving Approach-Based Training and Critical Thinking Training on Reducing Academic Self-Handicapping Behaviors and Academic Procrastination in Nursing Students with Test Anxiety - Ganjifard, Malihe; Jafar Tabatabaei, Samaneh Sadat; Jafar Tabatabaei, Toktam Sadat; Shahabizadeh, Fatemeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to compare the effectiveness of problem-solving approach-based training and critical thinking training on reducing academic self-handicapping behaviors and academic procrastination in nursing students with test anxiety. Methods and Materials: This research was a quasi-experimental study with a pretest-posttest design involving two intervention groups and one control group. The study population included nursing students with test anxiety in Birjand during the academic year 2022-2023. According to Cohen’s table, 36 students were selected through purposive sampling and randomly assigned to three groups. The measurement tools in this study included the Academic Procrastination Questionnaire (Savari, 2011) and the Academic Self-Handicapping Questionnaire (Schwinger & Stiensmeier-Pelster, 2011). The experimental groups underwent 8 sessions of 80-minute training based on problem-solving and critical thinking, while the control group received no such training. After the training period, a post-test was administered to all groups. The obtained data were analyzed using multivariate covariance analysis (MANCOVA) with SPSS statistical software. Findings: The study results showed that problem-solving and critical thinking training significantly reduced academic self-handicapping behaviors and academic procrastination in nursing students with test anxiety. However, no significant difference was found between the two training approaches regarding their effect on reducing academic self-handicapping behaviors and academic procrastination. Conclusion: This study demonstrated that both problem-solving approach-based training and critical thinking training significantly reduced academic self-handicapping behaviors and academic procrastination in nursing students with test anxiety. The effects of the interventions were maintained during follow-up, highlighting the long-term benefits of these methods. Given the critical role these skills play in improving academic performance and reducing negative behaviors, integrating problem-solving and critical thinking training into educational and clinical programs is recommended to enhance student outcomes and well-being.